Application of a bio‐based polyester plasticizer modified by hydrosilicon‐hydrogenation reaction in soft PVC films. (22nd January 2019) - Ji, Shufang; Gao, Chuanhui; Wang, Huizi; Liu, Yuetao; Zhang, Di; Zhang, Shanfa; Lu, Xiaotong; Wu, Yumin; Hu, Zunfu
Abstract : A kind of bio‐based plasticizer, poly (hexanediol maleic) (MH), was synthesized using 1, 6‐hexalene and maleic acid as raw materials, and it was modified by hydrosilicon‐hydrogenation reaction to improve its plasticizing efficiency. The chemical structure and plasticizing performance of MH and its modification product (MHA) were characterized by Fourier‐transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance ( 1 H‐NMR), X‐ray photoelectron spectroscopy (XPS), and Dynamic mechanical analysis (DMA). It was found that the hydrosilicon‐hydrogenation modification effectively improved the plasticizing efficiency of MH, reflecting on the decreased T g and the increased elongation at break of PVC blends. The migration resistance of PVC blends was tested and analyzed by solubility parameters, which revealed that the migration stabilities of PVC blends were promoted after modification. It was verified that the hydrogen bonding interaction between the CO group of plasticizers and α‐hydrogen of PVC exhibited in FTIR analysis was the main reason for the improvement of plasticizer performance of MH. Moreover, a new hydrogen bonding formed between SiOSi of MHA and the α‐hydrogen of PVC derived from XPS also caused the further improvement of plasticity for MHA.